Microfluidic automated plasmid library enrichment for biosynthetic gene cluster discovery. Issue 8 (25th February 2020) - Xu, Peng; Modavi, Cyrus; Demaree, Benjamin; Twigg, Frederick; Liang, Benjamin; Sun, Chen; Zhang, Wenjun; Abate, Adam R
Abstract: Microbial biosynthetic gene clusters are a valuable source of bioactive molecules. However, because they typically represent a small fraction of genomic material in most metagenomic samples, it remains challenging to deeply sequence them. We present an approach to isolate and sequence gene clusters in metagenomic samples using microfluidic automated plasmid library enrichment. Our approach provides deep coverage of the target gene cluster, facilitating reassembly. We demonstrate the approach by isolating and sequencing type I polyketide synthase gene clusters from an Antarctic soil metagenome. Our method promotes the discovery of functional-related genes and biosynthetic pathways.